The Influence of Interest and Learning Readiness on Learning Activities of High School Students In Chemistry Online Learning In South Sulawesi - Nurhardiyanti, Maddaung; A.K.Prodjosantoso, A.K.Prodjosantoso (Eduvest - Journal of Universal Studies, 2023)
This study aims to determine the effect of students' interest and readiness to learn on the learning activities of high school students in online chemistry learning in South Sulawesi. This research is quantitative research using the expost the facto method. The population of this research is all students of high school student majoring in science in South Sulawesi Province. The research sample was 402 students obtained by using two stage clustering random sampling method. Research data collection was carried out using questionnaires on learning interest, readiness to learn and learning activities of students during online learning of chemistry. Instrument were validated by using corrected item total correlation value. The reliability test used the Cronbach Alpha coefficient on the learning interest variable of 0.804, the learning readiness variable was 0.721 and the learning activity variable was 0.753 with a very high category. The data analysis technique used was path analysis. The findings indicated that interest in learning had a significant effect, accounting for 53.1% and 52.3% at a 5% significance level. Additionally, learning readiness demonstrated a 29% influence on learning activities at the same significance level. When combined, the total influence of both interest in learning and learning readiness on high school students' learning activities reached 67.6% at a 5% significance level. Overall, the study concluded that the impact of interest in learning and readiness to learn on learning activities was notably high.